Simultaneous Expression of PDH45 with EPSPS Gene Improves Salinity and Herbicide Tolerance in Transgenic Tobacco Plants - Garg, Bharti; Gill, Sarvajeet S.; Biswas, Dipul K.; Sahoo, Ranjan K.; Kunchge, Nandkumar S.; Tuteja, Renu; Tuteja, Narendra (Frontiers in Plant Science, 2017)
To cope with the problem of salinity- and weed-induced crop losses, a multi-stress tolerant trait is need of the hour but a combinatorial view of such traits is not yet explored. The overexpression of PDH45 (pea DNA helicase 45) and EPSPS (5-enoylpruvyl shikimate-3-phosphate synthase) genes have been reported to impart salinity and herbicide tolerance. Further, the understanding of mechanism and pathways utilized by PDH45 and EPSPS for salinity and herbicide tolerance will help to improve the crops of economical importance. In the present study, we have performed a comparative analysis of salinity and herbicide tolerance to check the biochemical parameters and antioxidant status of tobacco transgenic plants. Collectively, the results showed that PDH45 overexpressing transgenic lines display efficient tolerance to salinity stress, while PDH45+EPSPS transgenics showed tolerance to both the salinity and herbicide as compared to the control [wild-type (WT) and vector control (VC)] plants. The activities of the components of enzymatic antioxidant machinery were observed to be higher in the transgenic plants indicating the presence of an efficient antioxidant defence system which helps to cope with the stress-induced oxidative-damages. Photosynthetic parameters also showed significant increase in PDH45 and PDH45+EPSPS overexpressing transgenic plants in comparison to WT, VC and EPSPS transgenic plants under salinity stress. Furthermore, PDH45 and PDH45+EPSPS synergistically modulate the jasmonic acid (JA) and salicylic acid (SA) mediated signalling pathways for combating salinity stress. The findings of our study suggest that pyramiding of the PDH45 gene with EPSPS gene renders host plants tolerant to salinity and herbicide by enhancing the antioxidant machinery thus photosynthesis.